Mental illness-related stigma in healthcare: Barriers to access and care and evidence-based solutions. Issue 2 (March 2017) - Knaak, Stephanie; Mantler, Ed; Szeto, Andrew
Mental illness-related stigma, including that which exists in the healthcare system and among healthcare providers, creates serious barriers to access and quality care. It is also a major concern for healthcare practitioners themselves, both as a workplace culture issue and as a barrier for help seeking. This article provides an overview of the main barriers to access and quality care created by stigmatization in healthcare, a consideration of contributing factors, and a summary of Canadian-based research into promising practices and approaches to combatting stigma in healthcare environments.